The Effect of Parental Support on Student Learning Outcomes at the High School Level - Ma’rifatul Mahbubah, Siti; Arianto, Aji; Darmawan, Didit (LP2M IAI Al-Khairat Pamekasan, 2025)
This qualitative literature study aims to examine in detail the influence of parental support on student learning outcomes at the high school (SMA) level. Given the role of the student's family environment considered important in student learning, this study presents relevant literature such as journal articles, books, and research reports selected based on the quality and proximity of the topic. The analytical approach used is a narrative synthesis strategy to identify trends, themes, and insights to understand the contribution of parental support, such as emotional aspects, learning, and involvement. The conclusions of the literature review suggest that there is a strong positive association between different forms of parental support and improved learning achievement of high school students, although the mechanism and intensity of the effect vary depending on socioeconomic and cultural backgrounds. It is concluded that parental support is important in encouraging, enabling, and creating a supportive learning environment for high school students, so the implications of these findings underscore the importance of parent-school partnerships in initiatives to improve student academic performance.